PENGARUH INOVASI PRODUK DAN AKSES MODAL TERHADAP KINERJA KEUANGAN UMKM SEKTOR KULINER DI KECAMATAN SUKAJADI KOTA - Mochamad Izet Syahputra (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Culinary sector micro, small, and medium enterprises (MSMEs) play a strategic role in supporting local economic growth, particularly in urban areas. However, intense competition requires business actors to continuously innovate and obtain adequate access to capital to improve financial performance. This study aims to analyze the effect of product innovation and access to capital on the financial performance of culinary MSMEs in Sukajadi District, Bandung City. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to MSME owners and analyzed using multiple linear regression analysis. The results show that product innovation has a positive and significant effect on financial performance. Access to capital also has a positive and significant effect on financial performance. Simultaneously, product innovation and access to capital significantly influence the financial performance of culinary MSMEs. These findings indicate that the integration of innovation capability and capital accessibility is essential to enhance MSME competitiveness and business sustainability.Keywords: 5 words or phrases that reflect the contents of the article (alphabetically).